THU0069 In ra, becoming seronegative over the 1st year of dmard treatment does not translate to better chances of sustained drug-free remission in the long-term. (12th June 2018) - de Moel, E.C.; Derksen, V. F. A. M.; Trouw, L.A.; Bang, H.; Goekoop-Ruiterman, Y.P.; Steup-Beekman, G.M.; Huizinga, T.W.J.; Allaart, C.F.; Toes, R.E.M.; van der Woude, D.
Abstract : Background: In rheumatoid arthritis (RA), autoantibodies are a reflection of the underlying B cell autoimmunity and an important predictor of long-term outcome. Baseline seropositivity is a poor prognostic factor for sustained drug-free remission (SDFR). However, autoantibody levels may change and patients may become seronegative under treatment. It is unknown how often this happens and whether some autoantibodies (depending on isotype use or antigen recognition) disappear more often than others. Furthermore, it is unclear whether becoming seronegative early in disease, indicating disappearance of serological autoimmunity, improves chances of SDFR. Objectives: To longitudinally characterise the levels and presence of autoantibodies in RA patients and to investigate whether changes in these levels and/or presence associates with SDFR. Methods: In sera of 399 seropositive RA patients in the IMPROVED study 1, we measured, at 4-month-intervals over the first year of treatment: IgG, IgM, and IgA isotypes for anti-cyclic citrullinated peptide-2 (anti-CCP2) and anti-carbamylated protein antibodies (anti-CarP), IgM and IgA for rheumatoid factor (RF), and IgG autoantibodies against 4 citrullinated and 2 acetylated peptides. We investigated whether changes in antibody levels and seroconversion from positive to negative for each individual antibody was favourable for SDFR (drug-free DAS44 <1.6 lasting≥1 year until last follow-up). Results: For all 14 antibodies, median levels decreased significantly between baseline and 4 months and then stabilised. Most seroconversion to negative happened within the first 4 months of treatment (with prednisone and methotrexate), after which some patients converted back to seropositive. The prevalence of seroconversion varied substantially depending on the autoantibody. The percentage of patients who were seropositive at baseline and became seronegative by 12 months varied substantially depending on the autoantibody: 2% (anti-CCP2 IgG) to 66% (anti-CarP IgA) (see figure 1). We hypothesised that greater level decreases and seroconversion to negative might be favourable for the long-term outcome SDFR, but surprisingly, greater median decreases in levels were not associated with higher chance of SDFR for any antibody. Furthermore, using Chi-squared tests, we found no evidence that rates of SDFR were higher in patients who seroconverted to negative compared to those who stayed seropositive, for any of the 14 antibodies analysed (see figure 1). Conclusions: Autoantibody levels decrease and seroconversion from positive to negative occurs under treatment, but these changes do not translate to apparent clinical long-term benefits with regard to SDFR. This suggests that the disappearance of measurable serological autoimmunity does not lead to eradication of disease. Reference: [1] Heimans AR&T2016;18:23. Disclosure of Interest: None declared